Genome-Wide Identification and Analysis of the CCT Gene Family Contributing to Photoperiodic Flowering in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Wei Fu; Xinyu Jia; Shanyu Li; Yang Zhou; Xinjie Zhang; Lisi Jiang; Lin Hao (Horticulturae, 2025)
Photoperiod sensitivity significantly affects the reproductive process of plants. The CONSTANS, CONSTANS-LIKE, and TOC1 (CCT) genes play pivotal roles in photoperiod sensitivity and regulating flowering time. However, the function of the CCT gene in regulating flowering varies among different species. Further research is needed to determine whether it promotes or delays flowering under long-day (LD) or short-day (SD) conditions. CCT MOTIF FAMILY (CMF) belongs to one of the three subfamilies of the CCT gene and has been proven to be involved in the regulation of circadian rhythms and flowering time in cereal crops. In this study, 60 CCT genes in Chinese cabbage were genome-wide identified, and chromosomal localization, gene duplication events, gene structure, conserved domains, co-expression networks, and phylogenetic tree were analyzed by bioinformatics methods. The specific expression patterns of the BrCMF gene in different tissues, as well as the transcriptome and RT-qPCR results under different photoperiodic conditions, were further analyzed. The results showed that BrCMF11 was significantly upregulated in ebm5 under LD conditions, suggesting that BrCMF11 promoted flowering under LD conditions in Chinese cabbage. These findings revealed the function of the BrCCT gene family in photoperiod flowering regulation and provided a prominent theoretical foundation for molecular breeding in Chinese cabbage.